IMPROVING WRITING ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH COLLABORATIVE LEARNING METHOD AT THE EIGHTH GRADE STUDENTS OF MTsN 1 KOTA KEDIRI - citra, yeni yulia (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of this study was to find out whether Collaborative Learning method can improve the students’ writing achievement of descriptive text at the eighth grade students of MTs Negeri 1 Kota Kediri in Academic Year 2016/2017 or not. The class action research (CAR) was used to design this research. The data collection method were interview, observation, test, and field note. The subject of this research was the eighth grade in class VIII J with the total of students is 39. The results are that the mean of the first cycle is 63,4 and only 35,40% of the students who pass the success indicator while for the second cycle is 83,38 and 87.17% of the students who pass the success indicator. Based on the means of the first cycle and second cycle, there is significant improvement from the 63.4 to 83,38 and from 35.40% who pass the success indicator become 87.17%. From the results, it is recommended that by using collaborative learning method can improve the students’ writing achievement especially of descriptive text.